EFEK HIPOTENSIF FRAKSI KLOROFORMIK EKSTRAK ETANOLIK DAUN PEGAGAN (Centella asiatica (L.) Urban) PADA TIKUS TERINDUKSI FENILEFRIN - , HARWOKO ([Yogyakarta] : Universitas Gadjah Mada, 2013)
The hypertension cases in Indonesia that had not been diagnosed and reached yet by health care system were 75.8%. Antihypertensive herbs in scientification of âjamuâ contains Centella asiatica (L.) Urban. The leaf contains several compounds such as triterpenoids, flavonoids, phenolics, tannins, and resins. Reportedly, the total triterpenic fraction of C. asiatica can treat venous hypertensive microangiopathy, while ethyl acetate fraction of C. asiatica leaf has hypotensive effect in cats. This study aims to separate triterpenoid fraction of C. asiatica leaf from flavonoid fraction, to analyze asiaticoside contents, and to examine the hypotensive effect on phenylephrine-induced hypertensive rats. Ethanolic extract of C. asiatica leaf (EECA) was fractionated by chloroform to separate between triterpenoid fraction in the chloroformic fraction of C. asiatica leaf (CFCA) and flavonoid fraction in the chloroform insoluble fraction. Asiaticoside contents were then determined by TLC densitometry. As many as 40 male Wistar rats were grouped into 8 treatment groups: normal control (CMC-Na 0.5%), negative control (phenylephrine 0.9 mg/kg), positive control (captopril 2.5 mg/kg), CFCA doses of 5, 10, 15, 20 mg/kg, and EECA 400 mg/kg. Cardiovascular parameters such as systolic blood pressure (SBP), diastolic blood pressure (DBP), mean arterial pressure (MAP), and heart rate were measured by non-invasive tail-cuff method. The respon differences between groups were tested with one way ANOVA then followed by LSD at 95% level of confidence. The result showed that triterpenoid fraction of EECA could be separated from flavonoid fraction by fractionation with chloroform. The TLC-densitometric data showed that asiaticoside contents of CFCA were 0.402 Â± 0.02%. The CFCA showed hypotensive effect on phenylephrine-induced hypertensive rats. The highest hypotensive effect was 134% at dose 20 mg/kg. The ED50 values, a parameter of drug potency, of these effects on SBP, DBP and MAP were 7.79, 10.11, and 8.63 mg/kg, respectively.